Case report: Advanced primary squamous cell carcinoma in the periampullary area with upregulation of programmed cell death-ligand 1 expression and response to sintilimab immunotherapy - Wang, Baoshan; Li, Dazhou; Zeng, Dehua; Wang, Wen; Jiang, Chuanshen (Frontiers in Immunology, 2023)
Primary squamous cell carcinoma (SCC) of the periampullary area is exceedingly rare. We report a case of a 45-year-old woman who presented with progressive upper abdominal pain and melena. Laboratory testing revealed an elevated level of carcinoembryonic antigen. Esophagogastroduodenoscopy revealed a very large irregular ulcerated tumor in the periampullary area. Contrast-enhanced computed tomography (CT) of the chest, abdomen, and pelvis, 18 F-fluorodeoxyglucose positron emission tomography/CT, and thin-prep cytologic test excluded metastasis of the primary tumor to the periampullary area from other sites. Immunohistochemistry revealed positive p40 and cytokeratin (CK)5/6, indicating SCC. The expression of programmed cell death-ligand 1 (PD-L1) in tumor cells was upregulated, and the patient responded well to chemotherapy combined with immunotherapy. To the best of our knowledge, this is the first reported case of advanced primary SCC in the periampullary area with high expression of PD-L1.